Cultural Rights: A Bridge to Cosmopolitan Culture - Elyzabeth Bonethe Nasution (Universitas Pelita Harapan, 2025)
This paper examines the conceptual foundations of cultural rights by situating them within the evolving understanding of culture and the broader human rights discourse. Drawing from contemporary scholarship, the analysis demonstrates that culture has shifted from a static, group-bound notion toward a fluid, meaning-making process, a shift that significantly influences how cultural rights are theorized and justified. The paper identifies key strengths of cultural rights, including their ability to prevent human rights violations, protect minority communities from both forced assimilation and cultural oppression, preserve cultural diversity, and foster conditions for peaceful coexistence. At the same time, the paper highlights several conceptual limitations, such as the risks of cultural relativism, the instrumentalization of cultural rights by states, and the homogenizing pressures of globalization. By bringing these strengths and limitations into conversation with theories of cosmopolitanism, the paper argues that cultural rights have the potential to act as a bridge toward cosmopolitan culture—one characterized by mutual recognition, dialogue, and respect for diversity. Ultimately, this study suggests that while cultural rights are imperfect, their continued development and thoughtful implementation could meaningfully contribute to a more inclusive and globally connected cultural sphere.